Jezuītu izglītības principu salīdzinājums ar kristīgās mācības standartu Latvijā - Romančuka, Arta (Latvijas Universitāte, 2006)
Pētījuma „Jezuītu izglītības principu salīdzinājums ar kristīgās mācības standartu Latvijā” mērķis bija salīdzināt jezuītu izglītības principus ar kristīgās mācības koncepciju Latvijā. Pētījumā aplūkota jezuītu izglītības vēsturiskā attīstība, analizēts jezuītu izglītības pamatdokuments „Ratio Studiorum” un tā saistība ar Ignācija Lojolas „Garīgajiem vingrinājumiem”, apskatīta jezuītu izglītība mūsdienās un tās jaunais dokuments „Jēzus Sadraudzības izglītības raksturojums”. Jezuītu izglītības principi salīdzināti ar Latvijas pamatizglītības, ietverot arī kristīgo mācību, principiem, mērķiem un uzdevumiem. Darba gaitā veikti secinājumi, ka jezuītu izglītības un Latvijas pamatizglītības principi ir savietojami, tādēļ ierosināts jezuītu ieguldījumu izglītības attīstībā praktiski pielietot arī Latvijas izglītības sistēmā.

The goal of the research „The comparison of Jesuit educational principles with the syllabus of the subject of Christian education in Latvia” was to compare Jesuit educational principles with the principles of Christian education in Latvia. In this paper the historical development of the Jesuit education, the basic document of the Jesuit education „Ratio Studiorum” and its connection with Ignatius of Loyola’s „Spiritual Exercises” have been analysed. The contemporary Jesuit education and its document „The Characteristics of Jesuit Education” are inspected there. Jesuit educational principles are compared to principles, goals and tasks of primary education in Latvia, including the subject of Christian education. In the course of the research conclusions have been made about the correlation of Jesuit education and Latvia primary education principles. Suggestion has been made to apply Jesuit contribution in the development of education also to Latvia education system.
A comparison of the principles of Jesuit education with the Christian education standard in latvia
Keywords: Pedagoģija